Peran Pelatihan dan Pengembangan Sumber Daya Manusia dalam Meningkatkan Service Quality dalam Kinerja Perusahaan - Aditya Narayan; Harsya Maulana Fajrin; Pascal Kharua Albari; Mohamad Zein Saleh (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
In the midst of increasingly fierce business competition, companies need to continuously improve their service quality in order to maintain customer loyalty and gain a larger market share. The role of human resources (HR) has a vital role in improving service quality to excel, especially in interacting with customers. In this article, titled “The Role of Human Resources Training and Development in Improving Service Quality in Company Performance,” a literature review has helped the researcher to frame an in-depth analysis based on existing data to understand the contribution of employee training and development in improving service quality in the company. In addition to improving individual competencies, HR training and development also plays an important role in shaping an organizational culture that prioritizes service quality. Thus, companies need to pay serious attention to human resource training in order to continue to develop, as this is an important step in achieving success and sustainable growth.